Marcadores bioquímicos e de estresse oxidativo no fígado e nos rins de ratos submetidos a diferentes protocolos de utilização de esteroides anabolizantes - Dornelles, Guilherme Lopes (2016)
Anabolic androgenic steroids (AAS) are synthetic substances derived from testosterone that promote greater muscle mass and strenght. Thus, they are used illegally to improve athletic performance of horses, dogs or athletes or to improve meat production. The doses, ranging from 10 to100 times the therapeutic recommendation, enhances the deleterious effects on various organs. The objective of this study was to evaluate the effects of different protocols (P1, P2 and P3) of boldenone undecylenate (BU) and stanozolol (ST) on markers of liver and kidney function and variables of oxidative stress in these organs. For this, 54 male Wistar rats were divided into nine groups of six animals each. Each animal received intramuscularly 5.0 mg kg-1 of BU or ST once a week for four weeks (P1); 2.5 mg kg-1 of BU or ST once a week for eight weeks (P2); and 1.25 mg kg-1 of BU or ST once a week for 12 weeks (P3). For each protocol, a control group was used (CG), and they received 0.1 ml of olive oil intramuscularly. Blood, and fragments of liver and kidney were collected for alanine aminotransferase activity (ALT), alkaline phosphatase (ALP), albumin, creatinine, cholesterol, total protein, triglycerides, urea, reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS), total thiols (T-SH), and glutathione (GSH) evaluation. Seric ALT activity and cholesterol concentration were significantly (p<0.05) higher compared to CG when BU of protocol P1 was used. ALT activity was significantly higher (p<0.05) compared to the CG in protocol P2 when ST was used. Liver samples showed higher levels (p<0.05) of ROS and TBARS in protocols P1 and P3 when BU was used, and lower GSH activity (p<0.05) on group treated with protocol P3. Rats that have received ST under protocol P1 and P3 showed higher levels (p<0.05) of ROS, as well as increased TBARS levels in P3 but lower GSH activity in P3 (p<0.05) when compared to the CG. In the liver, the T-SH concentration was lower (p<0.05) in P2 when compared BU and ST of the CG. In renal tissues, ROS and TBARS levels were significantly higher (p<0.05) in animals that received BU under protocols P1 and P2; and GSH activity and T-SH levels were reduced in the three protocols (P1, P2 and P3). In addition, animals treated with ST occurred showed reduced renal levels of GSH levels (p<0.05) in P2 and P3. The treatment with ST also led to higher ROS levels (p<0.05) in P2 and P3, and TBARS levels in P3, but reduced concentration (p<0.05) of GSH levels in P2 and P3, and T-SH in P2 and P3. In conclusion, anabolic steroids are harmful even when used in low doses or in a few applications, since in all evaluated protocols was possible to observe changes in the redox balance in the liver and kidneys.